GE_GERICHTE C/21155/2018 vom 3. November 2020 - GE Cour de justice (2020)
ACTION EN PAIEMENT D'ENTRETIEN;DOMICILE;VISITE;OBLIGATION D'ENTRETIEN;ENFANT;REVENU HYPOTHÉTIQUE;INDICE DES PRIX À LA CONSOMMATION | CC.273; CC.274.al2; CC.276; CC.279; CC.285; CC.286.al1; CC.301a; CC.301a.al2.leta